Profile and Outcomes of Children with Acute Glomerulonephritis in Northwestern Nigeria - Olayinka Rasheed Ibrahım; Olajide Aladesua; Michael Abel Alao; Abdurrazzaq Alege (Çocuk Dergisi)
Objective: Studies on acute glomerulonephritis (AGN) in Nigeria described the epidemiological profile without an in-depth analysis of variables associated with outcomes. Herein, we describe the profile and factors associated with hospitalization outcomes (discharge or death) among childhood AGNs at a health facility in northwestern Nigeria. Material and Methods: This prospective cross-sectional study was conducted between 1st January 2018 and 31st December 2019 at a tertiary health facility in northwestern Nigeria. The diagnosis of AGN was based on a clinical diagnosis. We also obtained relevant history, clinical, and laboratory features. Results: Thirty-five children were admitted with AGN during the study period. The mean age was 7.7 ± 3.3 years. Most were aged 5 to 10 years (23; 65.7%), male (60.0%), and from a lower socio-economic class (77.2%). The annual incidence of AGN was 11 cases per 1000 children. The most common clinical presentations were generalized body swelling (100.0%), reduced urine output (85.7%), and hypertension (74.3%). The medians (interquartile range) of urea and creatinine were 10.0 (4.50 to 23.90) mmol/L and 85 (67.60 to 204.00) µmol/L, respectively. Among the clinical features, only fever was associated with outcomes, while serum urea and creatinine levels were significantly higher among non-survivors, p<0.05. We recorded four deaths (case fatality rate of 11.4%), two each from congestive cardiac failure and hypertensive encephalopathy.Conclusion: This study shows a high incidence of childhood AGN and mortality in Katsina, northwestern Nigeria. Fever was associated with outcomes, while serum creatinine and urea levels were elevated among non-survivors.